2010
DOI: 10.1074/jbc.m109.087254
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Mixed Esters of Butyric and Retinoic Acid Affording Myocardial Survival and Repair without Stem Cell Transplantation

Abstract: Possible cardiac repair by adult stem cell transplantation is currently hampered by poor cell viability and delivery efficiency, uncertain differentiating fate in vivo, the needs of ex vivo cell expansion, and consequent delay in transplantation after the onset of heart attack. By the aid of magnetic resonance imaging, positron emission tomography, and immunohistochemistry, we show that injection of a hyaluronan mixed ester of butyric and retinoic acid (HBR) into infarcted rat hearts afforded substantial cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 37 publications
(48 reference statements)
0
62
0
Order By: Relevance
“…Protein samples were prepared and immunoblots were analyzed as previously described [33]. Briefly, cells were lysed with M-PER extraction buffer supplemented with 1 mM phenylmethanesulfonyl fluoride, protease, and phosphatase inhibitor cocktail (Sigma-Aldrich).…”
Section: Sds/page and Western Blottingmentioning
confidence: 99%
“…Protein samples were prepared and immunoblots were analyzed as previously described [33]. Briefly, cells were lysed with M-PER extraction buffer supplemented with 1 mM phenylmethanesulfonyl fluoride, protease, and phosphatase inhibitor cocktail (Sigma-Aldrich).…”
Section: Sds/page and Western Blottingmentioning
confidence: 99%
“…Preconditioning with HBR of hMSCs ex vivo has also greatly increased the ability of these cells to repair infarcted hearts in both small (rats) and large (pig) animal models of post-infarct heart failure [35,53]. In subsequent studies, we have shown that the intramyocardial injection of HBR alone was even able to induce a substantial repair of the infarcted myocardial tissue, by acting on endogenous mechanisms of tissue regeneration and recruitment/activation of endogenous stem cells, without having to resort to stem cell transplantation [54].…”
Section: Tuning Human Cancer Stem Cell Dynamics With Chemical Agents:mentioning
confidence: 91%
“…This finding points at the relevant pleiotropic role of hyaluronic acid (HA) and glycosaminoglycans in the intracrine regulation of cell polarity and at the chance of using physical energies to preserve and direct this fundamental attribute of Life. HA has been used as a component to promote cardiogenesis in mouse embryonic [42] and human adult stem cells of different origin in vitro and in vivo [43][44][45] and to induce cardiac repair in vivo without stem cell transplantation in a rat model of myocardial infarction [46]. Accordingly, HAS2 suppression abolished the capability of human ES cells to differentiate in vitro along the cardiogenic and vasculogenic lineages [47].…”
Section: S4mentioning
confidence: 99%